Webinar: Addressing climate channge in agriculture possibilities for the future. - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2023)
Participants: Nekelia Gregore, moderator. Shalini Marahaj, moderator. Chaney St. Martin, International Specialist in Water and Soil Management